Nanostructured networks for energy storage: Vertically aligned carbon nanotubes (VACNT) as current collectors for high-power Li4Ti5o12(LTO)//LiMn2O4(LMO) lithium-ion batteries - Pawlitzek, Fabian; Althues, Holger; Schumm, Benjamin; Kaskel, Stefan (Batteries, 2017)
As a concept for electrode architecture in high power lithium ion batteries, self-supported nanoarrays enable ultra-high power densities as a result of their open pore geometry, which results in short and direct Li + -ion and electron pathways. Vertically aligned carbon nanotubes (VACNT) on metallic current collectors with low interface resistance are used as current collectors for the chemical solution infiltration of electroactive oxides to produce vertically aligned carbon nanotubes decorated with in situ grown LiMn 2 O 4 (LMO) and Li 4 Ti 5 O 12 (LTO) nanoparticles. The production processes steps (catalyst coating, VACNT chemical vapor deposition (CVD), infiltration, and thermal transformation) are all scalable, continuous, and suitable for niche market production to achieve high oxide loadings up to 70 wt %. Due to their unique transport structure, as-prepared nanoarrays achieve remarkably high power densities up to 2.58 kW kg −1 , which is based on the total electrode mass at 80 C for LiMn 2 O 4 //Li 4 Ti 5 O 12 full cells. The tailoring of LTO and LMO nanoparticle size ( 20–100 nm) and VACNT length (array height: 60–200 µm) gives insights into the rate-limiting steps at high current for these kinds of nanoarray electrodes at very high C-rates of up to 200 C. The results reveal the critical structural parameters for achieving high power densities in VACNT nanoarray full cells.
CRIS-Team Scopus Importer:2022-04-14
Keywords: High power lithium ion batteries Li; LiMn; Rate limiting steps; Self-supported nanoarrays; Vertically aligned carbon nanotubes